Mortality and Air Pollution Effects of Air Quality Interventions in Delhi and Beijing - Sinha, Jayati; Kumar, Naresh (Frontiers in Environmental Science, 2019)
Air pollution in the megacities of low and middle income (LMIC) countries has risen to the levels of public health hazards forcing them to take emergency measures, such as issuing red alerts and vehicle-rationing interventions (VRI). Using in-situ and high-resolution satellite data, this research shows that VRI reduced particulate matter (PM) ≤ 2.5 µm in aerodynamic diameter (PM2.5) in Beijing during the 2008 Summer Olympics. However, VRsI implemented in 2015 and 2016 in Beijing and in 2016 in Delhi were ineffective in improving air quality. The effects of VRI were short lived, for example 54% of the cleaning in Beijing disappeared within two weeks after the Olympics, and Delhi witnessed a 34% increase in PM2.5 during the two weeks after the interventions.